Specific resistivity of dislocations and vacancies for super-pure aluminium at 4.2 K determined in-situ and post-recovery deformation and correlated to flow stress. Issue 22 (17th November 2019) - Saimoto, Shigeo; Niewczas, Marek; Langille, Michael R.; Diak, Bradley
ABSTRACT: The evolution of dislocations during shape-change of metal forms results from microstructural shear mechanism that is essential to enhance ductility. However, at room temperatures for face-centred cubic metals, this evolution results in the generation of vacancies that tend to form nano-voids, the growth of which leads to ductile failure. The correlated occurrence of dislocations and vacancies may be differentiated using the change of resistivity with plastic strain at 4.2 K, because resistivity is very sensitive to single vacancies compared to the formation of stacking faulted defects and dislocations. In order to assess the microstructure, the specific resistivity of these defect species was measured at 4.2 K, whereby thermal recovery processes are non-existent. The resistivity per dislocation line-length per volume was determined to be 1.87 × 10 −25 Ωm 3 for super-pure aluminium. The change in resistivity directly correlated to the shear flow stress squared. Vacancy-like defects formed during plastic flow were correlated to the recoverable resistivity after 298 K anneal and the derived volume fraction (CV ) from mechanical data. The magnitude could be expressed as 12.9 × 10 −9 Ωm per CV in % or as 1.21 × 10 −25 Ωm 3 in terms of line-length of vacancies per volume. The choice of representation depends on the presumed vacancy distribution. However, the recoverable flow stress upon 298 K anneal only appear to be proportional to √ CV at low strains; that is, at high strains the generated vacancies had transformed to defects that give rise to a small decrease in resistivity but a more notable increase in the flow stress. The possible mechanisms for this transformation are discussed.